Standardization and in vitro Cytotoxic Studies on Narasimha lehiyam: A Potent Anticancer Siddha Drug - Ravichandran, N.; Rajalakshmi, P.; Davidraj, C.; Arun, K.P.; Brindha, P. (Asian Journal of Chemistry, 2014)
Cancer is one of the major killing disease, worldwide 10 million people were diagnosed every year with cancer. Chemical and radiation therapy are often recommemded treatments for cancer which often leads to a variety of side effects, hence herbal drugs are resolved to as an alternative therapy due its lesser side effects. But herbal drugs need standardization and validation studies. Narasimha lehiyam a herbal based Siddha formulation used to treat cancer, skin diseases, ulcer, leprosy, infectious diseases, glandular enlargement, dropsy, paralysis, diabetes, sinusitis, piles and pistula. The present paper was studied the standardization and validation point of view. Attempts were made to determine the quality parameters for this siddha formulation which include determination of organoleptic and physico chemical constants such as loss on drying, ash values and specific gravity. Besides total solid contents, fat contents, reducing sugars, alkaloids flavonoids, phenols, saponins and tannins were also estimated. The compounds present in the Narasimha lehiyam were identified using LC-MS/MS and GC-MS. The in vitro anticancer potential evaluated using MTT assay, the data of the results obtained were encouraging.